Struktur Pendanaan dan Profitabilitas: Studi pada Perusahaan Non-Keuangan yang Listing di Bursa Efek Indonesia - Irene Rini Demi Pangestuti; Dinar Nur Septiyanto (Jurnal Pasar Modal dan Bisnis, 2019)
Purpose- The study was conducted to examine the effect of capital structure on profitability. Variables of the capital structure are Long-term Debt to total assets (LTD), Short-term Debt to total assets (STD) and Debt to Equity Ratio (DER) while profitability is proxied by Return on Assets (ROA. Research is conducted on all Non-Financial companies listed on the Indonesia Stock Exchange (IDX) in the period 2014-2016. Methods- Use the Purposive Random Sampling technique to take samples. Samples taken from Bloomberg. The sample used amounted to 175 companies using multiple regression analysis SPSS program assistance. Finding- The results of the study note that LTD and STD have a significant negative effect on ROA. DER has not a significant positive effect on ROA.